Rhodamine B-based "turn-on" fluorescent and colorimetric chemosensors for highly sensitive and selective detection of mercury (II) ions - Wanichacheva N. (2014)
Two novel macromolecules based on 2-[3-(2-aminoethylsulfanyl)propylsulfanyl]ethanamine covalently bound to one and two units of rhodamine-B moieties, 1 and 2, were prepared and utilized as fluoroionophores and chromophores for the optical detection of Hg2+ ions. The sensors were readily prepared by a conventional two-step synthesis. Especially, sensor 1 exhibits high sensitivity and selective OFF-ON fluorescence enhancement and chromogenic change upon binding to Hg2+, which served as a "naked-eye" indicator by a noticeable color change of the solution (from colorless to pink-red color). 1 is shown to discriminate various competing metal ions, particularly Ag+ and Cu2+, as well as Cd2+, Na+, Li+, K+, Ba2+, Co2+, Ni2+, Mg2+, Mn2+ and Al3+, with a detection limit of 10ppb. © 2011 Elsevier B.V.